2004
DOI: 10.1038/sj.mp.4001537
|View full text |Cite
|
Sign up to set email alerts
|

A genome wide linkage study of obesity as secondary effect of antipsychotics in multigenerational families of eastern Quebec affected by psychoses

Abstract: Antipsychotics can induce in schizophrenic (SZ) and bipolar disorder (BP) patients serious body weight changes that increase risk for noncompliance to medication, and risk for cardiovascular diseases and diabetes. A genetic origin for this susceptibility to weight changes has been hypothesized because only a proportion of treated patients are affected, the degree of affection differing also in rates and magnitudes. In a first genome scan on obesity under antipsychotics in SZ and BP, we analyzed 21 multigenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 38 publications
2
35
0
1
Order By: Relevance
“…In fact, a large study of a multigenerational kindred (508 relatives) including members with BD or schizophrenia in Quebec, Canada, showed obesity to be 2.5 times more frequent in antipsychotictreated patients (30%) than in untreated family members (12%). 13 This finding suggests that medication plays a role in the development of obesity. By contrast, in a large epidemiological study comprising data from the general population (GP), the authors reported that drug-free BD relatives showed the highest frequency of MS, obesity, and abnormal glucose and diastolic blood pressure (BP) levels among several comparison groups, including drugtreated patients and their relatives.…”
Section: Introductionmentioning
confidence: 76%
“…In fact, a large study of a multigenerational kindred (508 relatives) including members with BD or schizophrenia in Quebec, Canada, showed obesity to be 2.5 times more frequent in antipsychotictreated patients (30%) than in untreated family members (12%). 13 This finding suggests that medication plays a role in the development of obesity. By contrast, in a large epidemiological study comprising data from the general population (GP), the authors reported that drug-free BD relatives showed the highest frequency of MS, obesity, and abnormal glucose and diastolic blood pressure (BP) levels among several comparison groups, including drugtreated patients and their relatives.…”
Section: Introductionmentioning
confidence: 76%
“…8,25 In another study, linkage for obesity was also found to 12q24 in patients on antipsychotic medication. 40 Recently, Li et al 41 have shown significant linkage for obesity-related traits: percentage fat (LOD 3.79; P ¼ 0.00001), BMI (LOD 2.98; P ¼ 0.0001) and waist circumference (LOD 2.86; P ¼ 0.00014) to chromosome 12q23 -24. Their fine-mapping data localized linkages for those traits to 116 -125 cM on chromosome 12.…”
Section: Discussionmentioning
confidence: 99%
“…276 Additionally, a genomewide linkage study of obesity in patients undergoing treatment with classical antipsychotics identified suggestive linkage (MLS = 2.74) at 12q24. 297 The gene coding for pro-melanin-concentrating hormone, involved in the control of food intake and energy regulation, is located near this region and is a potential candidate gene for drug-induced weight gain. A recent study found differences in genetic patterns associated with weight gain in olanzapine and risperidone treatment.…”
Section: Prediction Of Side Effectsmentioning
confidence: 99%
“…This approach has already been successfully used for the identification of genes related to warfarin dose-response levels 315 and to drug-induced weight gain. 297 Nevertheless, this strategy still requires genotyping of large number of variants in clinical samples of moderate-large size. Genotyping techniques have been adapted to these new necessities and a wide range of high-throughput methodologies are available.…”
Section: The Genomic Revolutionmentioning
confidence: 99%